Implementation of Psychoeducational-Based Arabic Language Maharah Kitabah Learning at MTsN Pacitan - Zain, Biqi Asshafah (Bilingua, 2025)
Arabic writing skills (mahārah al-kitābah) remain one of the most challenging aspects of language learning in Islamic schools, partly due to students’ anxiety, low confidence, and limited motivational support during instruction. This study aimed to explore how psychoeducational-based learning was implemented in the teaching of Arabic writing at MTsN Pacitan and how it influenced student engagement and competence. The study employed a qualitative descriptive design involving one Arabic teacher and 32 eighth-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis using validated observation sheets, interview guides, and review checklists. Data were analyzed thematically through coding and categorization. The results showed that psychoeducational elements were systematically embedded in learning activities through motivational dialogue, collaborative learning, reflective sharing, and supportive feedback. These practices reduced writing anxiety, strengthened confidence, and encouraged students’ active participation. Students gradually demonstrated greater autonomy and improvement in constructing Arabic sentences and short paragraphs. The findings indicate that writing competence develops more effectively when emotional readiness and psychological support accompany linguistic instruction. This study contributes to Arabic language pedagogy by highlighting the importance of integrating cognitive and affective learning dimensions. Future research is recommended to apply this model in broader contexts using mixed-method approaches.